Pengaruh Karakter Disiplin, Mandiri, Dan Kerja Keras Terhadap Kinerja Para Perajin Tembaga Di Tumang Desa Cepogo Kecamatan Cepogo Kabupaten Boyolali - Wiranto, Budi (2016)
Purpose to be achieved in this study was to determine the influence of discipline, self-contained, and hard work on the craft of copper in the village Tumang, Cepogo, Cepogo District of Boyolali. This research is quantitative, the method of proportional random sampling or sampling with random groups by using procedures lottery to determine the sample to determine the effect of the character of discipline, self-contained, and hard work on the performance of the craftsmen of copper in Tumang, Village Cepogo, District Cepogo , Boyolali. Sources of data in the study was obtained through observation, and examine documents or records. The validity of the data using techniques overtime. The calculation result known that the variable character of discipline gives the relative contribution of 56.6% and the effective contribution of 32.1%. Variable independent character gives the relative contribution of 5.1% and the effective contribution of 6%. Variable character hard work contributed relatively by 9.9% and the effective contribution of 13.1%. Copper craftsman performance can be improved by increasing the good discipline to support the achievement of the target.